2023
DOI: 10.3390/pharmaceutics15020470
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers in Mucoadhesive Eye Drops for Treatment of Dry Eye and Allergic Conditions: Application and Perspectives

Abstract: Dry eye syndrome and allergic conjunctivitis are the most common inflammatory disorders of the eye surface. Although eye drops are the most usual prescribed dosage form, they are characterized by low ocular availability due to numerous barrier mechanisms of the eye. The use of biopolymers in liquid ophthalmic preparations has numerous advantages, such as increasing the viscosity of the tear film, exhibiting bioadhesive properties, and resisting the drainage system, leading to prolonged retention of the prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 168 publications
0
1
0
Order By: Relevance
“…There has been a lot of pioneering work in this field, such as the development of mucoadhesive creams based on poly(acrylic acid) (PAAc) [202] and poly(methyl methacrylate) [203]. The majority of early research on mucoadhesion was done with traditional polymers in the form of tablets [204], powders [205,206], or films [207]. The promising results observed during the creation of these early mucoadhesive formulations suggested that mucoadhesion should be investigated further.…”
Section: Mucoadhesive Biomaterialsmentioning
confidence: 99%
“…There has been a lot of pioneering work in this field, such as the development of mucoadhesive creams based on poly(acrylic acid) (PAAc) [202] and poly(methyl methacrylate) [203]. The majority of early research on mucoadhesion was done with traditional polymers in the form of tablets [204], powders [205,206], or films [207]. The promising results observed during the creation of these early mucoadhesive formulations suggested that mucoadhesion should be investigated further.…”
Section: Mucoadhesive Biomaterialsmentioning
confidence: 99%
“…The turbidity of the dispersions was measured at 0.5, 1, 2, and 24 h and compared with the turbidity of the single mucin dispersion. The positively charged amino groups of CS reacted with negatively sialic acid residues present in the mucin causing the occurrence of precipitation, that is, reflected in a turbidity increase, indicating mucoadhesive properties [26,27].…”
Section: Mucoadhesive Evaluationmentioning
confidence: 99%
“…Thus, CS provides a useful excipient for producing mucoadhesive drug delivery systems to prolong the residence time [35]. One simple and easily performed method is based on turbidimetry [27]. Interactions between each type of CS-based NG and mucin were evidenced by the appearance of turbidity, which is denoted by increased absorbances in comparison with free mucin solution over time.…”
Section: Mucoadhesionmentioning
confidence: 99%
“…Hence, nanocarriers with strong mucoadhesive properties and excellent biocompatibility are vital for use in ophthalmic formulations. Mucoadhesive polymers, which have been demonstrated to bind with mucin through ionic interactions, van der Waals forces, or hydrogen bonding improve the ocular surface adhesion of the drug-carrying system and prolong the retention time of the drug, enabling efficient treatment for DE. , In particular, thiolated polymers, have been reported to have superior mucus-binding efficacy via their formation of disulfide linkages with cysteine-rich subdomains . This stable binding is further enhanced by interpenetration, enabling these polymers to anchor to the mucus mesh network.…”
Section: Introductionmentioning
confidence: 99%